2015
DOI: 10.1364/ol.40.000882
|View full text |Cite
|
Sign up to set email alerts
|

Improving cross-modal face recognition using polarimetric imaging

Abstract: We investigate the performance of polarimetric imaging in the long-wave infrared (LWIR) spectrum for cross-modal face recognition. For this work, polarimetric imagery is generated as stacks of three components: the conventional thermal intensity image (referred to as S0), and the two Stokes images, S1 and S2, which contain combinations of different polarizations. The proposed face recognition algorithm extracts and combines local gradient magnitude and orientation information f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 6 publications
0
29
0
Order By: Relevance
“…Fig. 1: Examples of (a) visible-LWIR pair [47], (b) visible-polarimetric pair [54], (c) visible-MWIR pair [47], and (d) visible-NIR pair [47].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 1: Examples of (a) visible-LWIR pair [47], (b) visible-polarimetric pair [54], (c) visible-MWIR pair [47], and (d) visible-NIR pair [47].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, recent works have been proposed to use the polarization-state information of thermal emissions to enhance the performance of thermal face recognition [18], [49], [54], [76]. It has been shown that polarimetric-thermal images capture geometric and textural details of faces that are not present in the conventional thermal facial imagery [54]. As a result, the use of polarization-state information can improves cross-spectrum recognition performance over using intensity-only information from conventional thermal imagers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that polarimetric thermal imaging captures additional geometric and textural facial details compared to conventional thermal imaging [10]. Hence, the polarization-state information has been used to improve the performance of cross-spectrum face recognition [10,27,30,35,26,5]. A polarimetric, referred to as Stokes images, is composed of three channels: S0, S1 and S2.…”
Section: Introductionmentioning
confidence: 99%
“…The large domain discrepancy between these images makes the cross-spectrum matching problem very challenging. Various methods have been proposed in the literature for crossspectrum matching [10,27,30,35,26,16,21,18,2,28,24].…”
Section: Introductionmentioning
confidence: 99%
“…The performance degradation is mainly due to the significant distributional change between the thermal and visible domains as well as a lack of sufficient data for training the deep networks for crossmodal matching. In many recent approaches, the polarization-state information of thermal emissions has been used to achieve improved cross-spectrum face recognition performance [9,27,31,36,26] since it captures geometric and textural details of faces that are not present in the conventional thermal facial images [31,9]. A polarimetric thermal image consists of four Stokes images: S 0 , S 1 , S 2 , and degree-of-linearpolarization (DoLP), where S 0 indicates the conventional total intensity thermal image, S 1 captures the horizontal and vertical polarization-state information, S 2 captures the diagonal polarization-state information and DoLP describes the portion of an electromagnetic wave that is linearly polarized [9].…”
Section: Introductionmentioning
confidence: 99%